Socioeconomic Profiles of Drivers of Heavy-Duty Vehicles and Self-Reported Causes of Road Traffic Crashes in Southwestern Nigeria - Fasaanu, Olusegun; olapoju, olabisi; Aguda, Samuel A. (Transportation Development Research, 2025)
Heavy-duty vehicle (HDV) crashes, particularly those involving tankers and trailers, present severe safety challenges in Nigeria due to the combination of human, vehicular, and infrastructural risk factors. This study investigates the socioeconomic and demographic characteristics of HDV drivers in Southwestern Nigeria and examines their perceptions of factors contributing to road traffic crashes. Using a descriptive survey design, data were collected from 200 licensed tanker and trailer drivers across major haulage corridors through structured questionnaires. Descriptive statistics, Relative Importance Index (RII), and Analysis of Variance (ANOVA) were employed to analyze the data. Findings revealed an entirely male driver population, predominantly aged 31–60 years, with substantial driving experience (over 70% having more than 10 years). Most operated company-owned (44%) or privately owned (53.5%) vehicles, the majority of which were termed ‘fairly used’ (68%). Poor road conditions (RII = 0.87), long driving hours and fatigue (RII = 0.86), and mechanical faults (RII = 0.85) emerged as the most critical perceived causes of crashes, followed by employer time pressure, substance use, and lack of rest facilities. ANOVA results indicated significant differences in accident involvement across age groups (p = 0.005) and driving experience levels (p = 0.009), with younger and less experienced drivers reporting higher accident rates. The findings underscore the need for targeted driver training, stricter enforcement of rest regulations, improved road infrastructure, and fleet maintenance standards. These insights are vital for policymakers and transport stakeholders seeking to reduce HDV-related crash risks in Nigeria’s freight sector.